Meaning Relations in the Novel Harga sebuah percaya by Tere Liye, How to Integrate Semantic Learning in University? - Heny Kusuma Widyaningrum; Cahyo Hasanudin; Cerianing Putri Pratiwi; Froilan D. Mobo (Jurnal Pendidikan Edutama, 2024)
Meaning relations are semantic connections or connections between words, phrases, or concepts that appear in a text. The aim of this research is to describe the types of meaning relaxation in the novel Harga a Confidence by Tere Liye and to integrate it into semantic learning in higher education. This research uses a descriptive method. The data for this research are quotations from sentences in the novel Harga a Confidence by Tere Liye which contain meaning relationships, documentation and interviews. The research procedure uses six steps. The data analysis technique uses six analysis steps. The conclusions of this research are 1) Tere Liye's novel Harga a Confidence found the types of meaning relations of epizeuksis repetition, synonyms, antonyms, equivalence (equivalence of words), and collocations (comparison of words), and 2) forms of integration in semantic learning in higher education can be carried out through 9 steps, namely (1) Identifying the Concept of Meaning Relations, (2) Preparing Learning Modules, (3) Linking it to Semantic Concepts in General, (4) Introduction to Case Studies, (5) Active Learning, (6) Text Analysis Tasks, (7) Reflective Discussion, (8) Presentation of Results, (9) Evaluation.